Peran Pendidikan Agama Islam dalam Pembentukan Karakter Anak Bangsa - Alfarizi, Angga; Zikrah, Ilman; Dwi Putri, Melina; Agustina, Tessa; Tamara, Tiwi (UIN Fatmawati Sukarno Bengkulu, 2025)
This article will discuss the role of Islamic religious education in schools in shaping students' personalities. Islamic Religious Education (PAI) is one of the important pillars in character education. Character education will develop well if it starts with cultivating a religious spirit in children, therefore PAI material in schools is one of the supports for character education. Islamic religious education is one of the media that can be used in the world of education to develop the character of students. This research uses the Library Research Method, data collection techniques obtained from library sources in the form of journals. Education according to Islamic teachings aims to develop personality and shape the character of the younger generation, this is very necessary because the next generation will have a noble future accompanied by good morals or what in Islam is called Akhlakul Karimah. In the family environment, parents have a very important role in developing personality and shaping the personality of the nation's generation, especially their children.